Defining Normal Liver Stiffness Range in a Normal Healthy Chinese Population without Liver Disease - Fung, James; Lee, Cheuk-kwong; Chan, Monica; Seto, Wai-kay; Wong, Danny Ka-ho; Lai, Ching-lung; Yuen, Man-fung (PloS one, 2013)
For patients with chronic liver disease, different optimal liver stiffness cut-off values correspond to different stages of fibrosis, which are specific for the underlying liver disease and population. To establish the normal ranges of liver stiffness in the healthy Chinese population without underlying liver disease. This is a prospective cross sectional study of 2,528 healthy volunteers recruited from the general population and the Red Cross Transfusion Center in Hong Kong. All participants underwent a comprehensive questionnaire survey, measurement of weight, height, and blood pressure. Fasting liver function tests, glucose and cholesterol was performed. Abdominal ultrasound and transient elastography were performed on all participants. Of the 2,528 subjects, 1,998 were excluded with either abnormal liver parenchyma on ultrasound, chronic medical condition, abnormal blood tests including liver enzymes, fasting glucose, fasting cholesterol, high body mass index, high blood pressure, or invalid liver stiffness scan. The reference range for the 530 subjects without known liver disease was 2.3 to 5.9 kPa (mean 4.1, SD 0.89). The median liver stiffness was higher in males compared with females (4.3 vs 4.0 kPa respectively, p<0.001). There was also a decline in median Lliver stiffness in the older age group, from 4.2 kPa in those <25 years to 3.4 kPa for those >55 years (p=0.001). The healthy reference range for liver stiffness in the Chinese population is 2.3 to 5.9 kPa. Female gender and older age group was associated with a lower median liver stiffness.